2012
DOI: 10.1038/nsmb.2418
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of repair of 5′-topoisomerase II–DNA adducts by mammalian tyrosyl-DNA phosphodiesterase 2

Abstract: The Topoisomerase II (topo II) DNA incision and ligation cycle can be poisoned (e.g following treatment with cancer chemotherapeutics) to generate cytotoxic DNA double strand breaks (DSBs) with topo II covalently conjugated to DNA. Tyrosyl-DNA phosphodiesterase 2 (Tdp2) protects genomic integrity by reversing 5′-phosphotyrosyl (5′-Y) linked topo II-DNA adducts. Here, X-ray structures of mouse Tdp2-DNA complexes reveal that a Tdp2 β-2-helix-β DNA damage binding “grasp”, helical “cap”, and DNA lesion binding ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
111
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(122 citation statements)
references
References 40 publications
11
111
0
Order By: Relevance
“…5F). These results are consistent with the crystal structures for TDP2, showing the enzyme has a narrow DNA binding pocket, optimal for accessing single-stranded DNA ends (26,27).…”
Section: Ribonucleotide Incorporation Enhances Irreversible Top2cc Busupporting
confidence: 80%
See 2 more Smart Citations
“…5F). These results are consistent with the crystal structures for TDP2, showing the enzyme has a narrow DNA binding pocket, optimal for accessing single-stranded DNA ends (26,27).…”
Section: Ribonucleotide Incorporation Enhances Irreversible Top2cc Busupporting
confidence: 80%
“…TDP2-RNA⅐DNA Complex Crystallization-Expression of the mouse TDP2 catalytic domain (mTdp cat residues 118-370) for crystallization was carried out as described (26). The TDP2-RNA⅐DNA complex was crystallized using a dual one nucleotide 5Ј-overhang crystallization strategy (26) and a 5Ј-phosphorylated self-annealing oligonucleotide.…”
Section: ј-Linked Peptidyl Substrate Preparation and Tdp2mentioning
confidence: 99%
See 1 more Smart Citation
“…2B). The preference of TDP2 for 5′ phosphotyrosyl bonds is consistent with recent X-ray data (27)(28)(29), but TDP2 also is active on 3′-substrates (20,26,30). Although TDP2 likely is the only enzyme of its kind (30), complete knockout of TDP2 in chicken DT40 cells and in mice was not lethal (20), possibly reflecting the power of redundancy in DNA repair.…”
supporting
confidence: 71%
“…It has also been reported that the multifunctional enzyme Tdp2 (also known as TTRAP or EAPII) is more efficient in catalyzing the resolution of 5Ј-phosphotyrosyl adducts than Tdp1 (39). However, Tdp2 is a member of the exonuclease-endonucleasephosphatase (or EEP) nuclease family that uses single Mg 2ϩ -dependent catalysis to cleave the 5-phosphotyrosine bond and functions in the nonhomologous end joining pathway (40,41). Thus, Tdp1 and Tdp2 constitute complementary DNA repair activities, with distinct reaction mechanisms (27,42,43).…”
Section: Discussionmentioning
confidence: 99%